THE ROLE OF HISTORICAL MEMORY IN THE STUDY OF SOCIO-PHILOSOPHICAL HERITAGE - Otabek Ortikov (American Journals Publishing, 2023)
The article reveals the importance of historical memory in the study of socio-philosophical heritage. At the same time, the interrelationship with the concepts of nation, people, socio-spiritual environment is highlighted in the historical memory. In this case, the role of incentives is correctly indicated.
Keywords: Socio-philosophical heritage, historical memory, retrospective information, thinkers, subject, historical-philosophical heritage, stimulus-tools